Simulating business processes for descriptive, predictive, and prescriptive analytics - Greasley, Andrew (De G Press, 2019)
This book outlines the benefits and limitations of simulation, what is involved in setting up a simulation capability in an organization, the steps involved in developing a simulation model and how to ensure model results are implemented. In addition, detailed example applications are provided to show where the tool is useful and what it can offer the decision maker. --